The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1516-89132003000100003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nomuraea rileyi strains using polymorphic DNA, virulence and enzyme activity

Abstract: The characterization of entomopathogenic microorganisms is important for the selection of more effective strains for use in integrated pest-control programs. Five Nomuraea rileyi strains (SA86101, GU87401, SR86151, CG128 and VA9101) were characterized using random amplified polymorphic DNA (RAPD) analysis, virulence studies and assessment of chitinolytic and proteolytic activity. RAPD analysis divided the strains into two groups with a similarity coefficient of 0,76%, group 1 consisting of strains SA86101, GU8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…In order to better understand the pathogen-host relationships of this mycopathogen, various molecular methods have been used to delineate strains of N. rileyi. For example, DNA extracted from diVerent pools of N. rileyi isolates have been subjected to random ampliWed polymorphic DNA (RAPD) (Tigano and Aljanabi, 2000;Vargas et al, 2003), inter-simple sequence repeat (ISSR) analysis (Han et al, 2002) and ampliWed fragment length polymorphism (AFLP) (Boucias et al, 2000a,b). Vargas et al (2003) were unable to link the results of RAPD analysis conducted on a series of N. rileyi isolates to phenotypic traits (virulence, enzyme levels).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the pathogen-host relationships of this mycopathogen, various molecular methods have been used to delineate strains of N. rileyi. For example, DNA extracted from diVerent pools of N. rileyi isolates have been subjected to random ampliWed polymorphic DNA (RAPD) (Tigano and Aljanabi, 2000;Vargas et al, 2003), inter-simple sequence repeat (ISSR) analysis (Han et al, 2002) and ampliWed fragment length polymorphism (AFLP) (Boucias et al, 2000a,b). Vargas et al (2003) were unable to link the results of RAPD analysis conducted on a series of N. rileyi isolates to phenotypic traits (virulence, enzyme levels).…”
Section: Introductionmentioning
confidence: 99%
“…For example, DNA extracted from diVerent pools of N. rileyi isolates have been subjected to random ampliWed polymorphic DNA (RAPD) (Tigano and Aljanabi, 2000;Vargas et al, 2003), inter-simple sequence repeat (ISSR) analysis (Han et al, 2002) and ampliWed fragment length polymorphism (AFLP) (Boucias et al, 2000a,b). Vargas et al (2003) were unable to link the results of RAPD analysis conducted on a series of N. rileyi isolates to phenotypic traits (virulence, enzyme levels). Tigano and Aljanabi (2000) using RAPDs were able to clearly delineate N. rileyi into two phenetic groups that were associated with the insect host.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting products are separated by gel electrophoresis, which provides RAPD-banding profiles that allow to analyze presence or absence of bands. This profiling technique has been widely employed to study intraspecific variation within species like Entomophaga grylli (Entomophthoromycotina: Entomophthorales) (Bidochka et al 1995), E. muscae (Jensen et al 2001), P. neoaphidis (Rohel et al 1997;Nielsen et al 2001;Tymon and Pell 2005), Zoophthora phytonomi (Entomophthoromycotina: Entomophthorales) (Hajek et al 1996), Z. radicans (Hodge et al 1995), B. bassiana (Maurer et al 1997;Fernandes et al 2006), B. brongniartii (Cravanzola et al 1997Piatti et al 1998), Hirsutella thompsonii (Ascomycota: Hypocreales) (Mozes-Koch et al 1995;Aghajanzadeh et al 2007), L. lecanii (Mor et al 1996), M. anisopliae (Fegan et al 1993;Leal et al 1994;Velásquez et al 2007), N. rileyi (Boucias et al 2000Vargas et al 2003), and Paecilomyces farinosus (=Isaria farinosus) (Ascomycota: Hypocreales) (Chew et al 1998). Studies have focused for instance on associations of fungal genotypes with specific hosts (Hodge et al 1995;Bridge et al 1997;Maurer et al 1997;Jensen et al 2001) or on correlations between RAPD profiles and geographical origin of a species (Leal et al 1994;Hajek et al 1996;Boucias et al 2000;Nielsen et al 2001).…”
Section: Randomly Amplified Polymorphic Dnamentioning
confidence: 99%
“…The full potential of entomopathogenic fungi has not been approached. However, previous studies indicate that the insect mycopathogen N. rileyi a dimorphic hypomycete causes fungal epizootics in population of several noctuid pests (14,28,31). Moreover, previous bioassays have shown that N. rileyi isolates from different geographical locations and different hosts vary in their virulence and specificity (3,12,30,34).…”
Section: Introductionmentioning
confidence: 99%